2021
DOI: 10.1371/journal.pone.0243683
|View full text |Cite
|
Sign up to set email alerts
|

Analytical validation and performance characteristics of a 48-gene next-generation sequencing panel for detecting potentially actionable genomic alterations in myeloid neoplasms

Abstract: Identification of genomic mutations by molecular testing plays an important role in diagnosis, prognosis, and treatment of myeloid neoplasms. Next-generation sequencing (NGS) is an efficient method for simultaneous detection of clinically significant genomic mutations with high sensitivity. Various NGS based in-house developed and commercial myeloid neoplasm panels have been integrated into routine clinical practice. However, some genes frequently mutated in myeloid malignancies are particularly difficult to s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
1
3
Order By: Relevance
“…The gene mutation structure was differed slightly from a recent study; the study demonstrated ASXL1, SRSF2 , and TET2 mutations were more common 17 . NPM1, DNMT3A, FLT3 , and NRAS had a high mutation frequency in AML 6,18 . In this study, epigenetic abnormalities were the most prominent in ML, where TET2, ASXL1, GATA2 , and FLT3 had the highest mutation frequency (≥20%), followed by NPM1, NRAS , and DNMT3A (10%–20%); the results were slightly different from those of previous studies; however, these genes are common in AML.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The gene mutation structure was differed slightly from a recent study; the study demonstrated ASXL1, SRSF2 , and TET2 mutations were more common 17 . NPM1, DNMT3A, FLT3 , and NRAS had a high mutation frequency in AML 6,18 . In this study, epigenetic abnormalities were the most prominent in ML, where TET2, ASXL1, GATA2 , and FLT3 had the highest mutation frequency (≥20%), followed by NPM1, NRAS , and DNMT3A (10%–20%); the results were slightly different from those of previous studies; however, these genes are common in AML.…”
Section: Discussioncontrasting
confidence: 96%
“… 17 NPM1, DNMT3A, FLT3 , and NRAS had a high mutation frequency in AML. 6 , 18 In this study, epigenetic abnormalities were the most prominent in ML, where TET2, ASXL1, GATA2 , and FLT3 had the highest mutation frequency (≥20%), followed by NPM1, NRAS , and DNMT3A (10%–20%); the results were slightly different from those of previous studies; however, these genes are common in AML.…”
Section: Discussioncontrasting
confidence: 93%
“…Although they performed WES sequencing with greater genome coverage, the number of somatic variants was relatively low, especially in the myeloid-related genes included in our targeted NGS panel. The number of somatic mutations detected in our cohort was lower than in other studies with similar targeted myeloid panel designs [16,51].…”
Section: Discussioncontrasting
confidence: 82%
“…As a joint effort to keep up with state-of-the-art genomic characterization of myeloid malignancies, Genomic Medicine Sweden (GMS), a national initiative in precision medicine, in collaboration with the SciLifeLab Clinical Genomics platform, is currently developing and harmonizing the use of larger, capture-based gene panels for improved cancer diagnostics [18]. Most gene panels currently used in diagnostics of hematologic malignancies are PCR amplicon-based and rely on a small, fixed gene content (e.g., 40-70 genes) [19][20][21][22][23][24][25][26]. Probe-based capture enrichment, however, has several advantages compared with PCR amplicon-based, as it is easier to update, displays a much more even target-coverage, allows larger content to similar sequencing capacity, and performs especially well across complex, repetitive regions, and GCrich areas.…”
Section: Introductionmentioning
confidence: 99%